A comparative study of library services for the visually and physically handicapped in city libraries in Metro Manila - Angala, Reiner V.; Sison, Josephine C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This study sought to find out if Public City Libraries had services for the blind and physically disabled and compare their services to find out which of these libraries best serves the blind and physically disabled patrons in terms of facilities, equipment, collection, staff and services. The main data-gathering instrument used in this study was the checklist taken from a proposed standard public library services for the blind and physically disabled adapted from by the researcher based on existing public library standards for the blind and physically disabled of the American Library Association. To analyze the data gathered, all present facilities, equipment, collection, staff and services were marked as a check m ark on the checklist and added up in each category. The total number of checks must be at least sixty percent (60 percent) of the total number of items in the category for the particular public library service to pass the evaluation for the category.
The study included eleven (11) Public City Libraries in Metro Manila, namely: the Caloocan City Public Library, Las Pi¤as City Public Library, Makati City Public Library, Mandaluyong City Public Library, Manila City Public Library, Marikina City Public Library, Paranaque City Public Library, Pasay City Public Library, Quezon City Public Library and the Valenzuela City Public Library.
From the findings of the study, all libraries have the basic services for "normal" and handicapped patrons but no special services for the blind and physically disabled patrons.
After all the data of the libraries were compared, the library that best met the proposed standards are the following: (1) Facilities - Pasig City Public Library; (2) Equipment - all libraries rank the same except for the Manila City Public Library which does not carry any of the proposed standard equipment; (3) Collection - the Makati, Pasig and Quezon City Public Libraries; (4) Staff - none of the libraries passed this category; and (5) Services - the Marikina, Pasig and Quezon City Public Libraries.
From the findings of the study, the following conclusions may be stated: Public City Libraries in Metro Manila do not have services specifically for the blind and physically handicapped because no standards have been implemented by the National Library; present facilities may accommodate blind and disabled persons but gives difficulty because of constraints like the absence of ramps/elevators; collections are adequate for most physically disabled persons but none have materials suitable for the blind patrons; the libraries have only basic services but no special services for the blind and physically disabled users of the library.
To improve the library services for the blind and physically disabled, the following recommendations are being given: The National Library should create minimum public library standards for the blind and physically disabled in public city libraries; public libraries should observe the Accessibility Law of 1983; public library staff must be oriented on Republic Act 7277 to give them better understanding of the needs of the blind and physically disabled patrons; a compromise of facilities provided so that public libraries can accommodate both normal and the blind and physically disabled users of the library; finally, the proposed standards for services are strongly recommended as bases for drawing up needed standards for public libraries to be spearheaded by The National Library.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and handicapped children; Libraries and the blind; Public libraries--Philippines--Metro Manila